Techno-economic analysis of low-carbon hydrogen production by sorption enhanced steam methane reforming (SE-SMR) processes - Yan, Yongliang; Manovic, Vasilije; Anthony, Edward J.; Clough, Peter T. (Elsevier, 2020)
Hydrogen is an attractive energy carrier that will play a key role in future global energy transitions. This work investigates the techno-economic performance of six different sorption enhanced steam methane reforming (SE-SMR) configurations integrated with an indirect natural gas or biomass-fired calciner, oxy-fuel combustion and chemical-looping combustion for large-scale blue and carbon-negative hydrogen production. The techno-economic performance of the proposed cases was evaluated by their net efficiency, CO2 capture efficiency, levelised cost of hydrogen (LCOH), and costs of CO2 avoided and removal. A sensitivity analysis was also conducted to evaluate the key parameters and explore existing uncertainties that can affect the economic performance of the proposed SE-SMR processes. The results revealed that the proposed systems were comparable with conventional steam methane reforming (SMR) with carbon capture and storage (CCS). The LCOH of the proposed SE-SMR plants ranged from £1.90–2.80/kg, and the costs of CO2 avoided and removal ranged from £33-69/tonne and £58-107/tonne, respectively. By applying a carbon price (£16/tonne CO2), the costs of CO2 avoided and removal for the proposed SE-SMR processes could be significantly reduced. The results of cumulative discounted cash flow of SE-SMR plants at a hydrogen selling price of £3.00/kg indicated that all the investment of the proposed cases could be paid back after eight years, even if the carbon tax is zero.
Keywords: Blue hydrogen production; Sorption enhanced steam methane reforming; Carbon capture; Techno-economic analysis